2019
DOI: 10.3390/ijerph16050708
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Cognitive Behavior Therapy for Young Taiwanese Female Nursing Students with Irritable Bowel Syndrome—A Cluster Randomized Controlled Trial

Abstract: Irritable Bowel Syndrome (IBS) is prevalent within the general population. Studies have shown that stress and anxiety co-exist with IBS. Young Taiwanese women commonly exhibit physical and psychological health problems caused by academic stress. The purpose of our current study was to evaluate the efficacy of short-term Internet-delivered cognitive-behavioral therapy (ICBT) on female nursing students in practicum. We performed a cluster randomized controlled trial comprised of 160 participants who met the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 49 publications
0
31
1
3
Order By: Relevance
“…Elementos que compõem a avaliação da ansiedade em estudantes de enfermagem Instrumentos Akca et al, 2015;Alshammari, 2019;Augner, 2011;Baksi et al, 2017;Gebhart et al, 2020;Hollenbach, 2016;Hsiung D-Y et al, 2019;Kavurmaci et al, 2015;Lee et al, 2019;Lima et al, 2017;Mojarrab et al, 2020;Plaiti et al, 2016;Prado et al, 2012;Prato & Yucha, 2013;Rajagopal, Pugazhanthi, & George, 2012;Sancar et al, 2018 O elevado número de estudos envolvendo a ansiedade no contexto acadêmico pode se dar pela relação direta da ansiedade com o desempenho educacional dos estudantes. Quando se deparam com sentimento de competividade, atrelados às exigências e cobranças quanto ao futuro profissional, os estudantes podem experenciar certas desordens (Chaves et al, 2015;Costa et al, 2017;Son et al, 2019).…”
Section: Referênciasunclassified
See 2 more Smart Citations
“…Elementos que compõem a avaliação da ansiedade em estudantes de enfermagem Instrumentos Akca et al, 2015;Alshammari, 2019;Augner, 2011;Baksi et al, 2017;Gebhart et al, 2020;Hollenbach, 2016;Hsiung D-Y et al, 2019;Kavurmaci et al, 2015;Lee et al, 2019;Lima et al, 2017;Mojarrab et al, 2020;Plaiti et al, 2016;Prado et al, 2012;Prato & Yucha, 2013;Rajagopal, Pugazhanthi, & George, 2012;Sancar et al, 2018 O elevado número de estudos envolvendo a ansiedade no contexto acadêmico pode se dar pela relação direta da ansiedade com o desempenho educacional dos estudantes. Quando se deparam com sentimento de competividade, atrelados às exigências e cobranças quanto ao futuro profissional, os estudantes podem experenciar certas desordens (Chaves et al, 2015;Costa et al, 2017;Son et al, 2019).…”
Section: Referênciasunclassified
“…Este compreende 20 itens em cada uma de suas subescalas: ansiedade estado (IDATE-E) e ansiedade traço (IDATE-T), e cada item pode ser classificado a partir de uma escala tipo likert de quatro pontos. Assim, a pontuação total do instrumento pode variar de 20 a 80 (Akca et al, 2015;Alshammari, 2019;Baksi et al, 2017;Gebhart et al, 2020;Hollenbach, 2016;Hsiung et al, 2019;Kavurmaci et al, 2015;Lee et al, 2019;Mojarrab et al, 2020;Plaiti et al, 2016;Prato & Yucha, 2013;Sancar et al, 2018;Sharma & Sharma, 2015;Son et al, 2019). Torna-se importante salientar que, apesar de avaliar a ansiedade traço e estado, observa-se, em alguns estudos, a aplicação de somente uma subescala, a exemplo da IDATE-E (Mojarrab et al, 2020;Son et al, 2019).…”
Section: Referênciasunclassified
See 1 more Smart Citation
“…Lee et al [ 19 ] evaluated the efficacy of short-term internet-delivered cognitive–behavioral therapy (ICBT) on female nursing practicum students with irritable bowel syndrome. They performed a cluster randomized controlled trial comprising 160 participants, which were divided into three groups: (1) ICBT, (2) expressive writing (EW), and (3) wait-list control.…”
Section: The Work Includedmentioning
confidence: 99%
“…In view of the limited healthcare resources and its high costs and increasing demand, online or internet-delivered CBT approaches have been proposed. Generally the use of online/internet based therapies is controversial, but according to their supporters, such interventions can overcome many existing barriers and provide at least short-term effectiveness in managing depression and anxiety [73,74]. However, a systematic review has revealed no sufficient evidence for the effectiveness of online CBT in GI disorders, including IBS [75].…”
Section: Psychological Assistance and Psychotherapymentioning
confidence: 99%